Implementasi Permendagri Nomor 66 Tahun 2007 Tentang Penyusunan Rencana Kerja Pembangunan Desa Di Desa Kenteng Kecamatan Bandungan Kabupaten Semarang - Bahtiar, Agung; Santoso, R. Slamet (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Research Policy Implementation Village Development Work Plan in District Bandungan a qualitative descriptive study. This study uses the precision of a policy to explain the effectiveness of policy implementation Village Development Work Plan. The focus of this research that the Policy Implementation Village Development Work Plan in Kenteng Village District Bandungan using George Edwards III implementation model to analyze the factors in the implementation of policies that are used to determine the success of the policy implementation process. Informants in this study is from Village Head, LPM (Institute of community empowerment), BPD (Village Deliberation State), Citizens, Executive Boards dan KPM (Community Empowerment Cadres). Research and analysis process begins from the state of development, describe the implementation process by using the appropriateness of the policy to assess the effectiveness and efficiency of policies Village Development Work Plan. Furthermore, analyzing the factors implementations using George Edwards III models to be able to see the success of the implementation of the policy Village Development Work Plan. With so can find out shortcomings in the implementation process so that it can be improved so that the implementation of a policy Village Development Work Plan can run effectively and efficiently.